Highly multiplexed molecular inversion probe panel in Plasmodium falciparum targeting common SNPs approximates whole-genome sequencing assessments for selection and relatedness - Niaré, Karamoko; Crudale, Rebecca; Fola, Abebe A.; Wernsman Young, Neeva; Asua, Victor; Conrad, Melissa D.; Gashema, Pierre; Ghansah, Anita; Hangi, Stan; Ishengoma, Deus S.; Mazarati, Jean-Baptiste; Zeleke, Ayalew Jejaw; et al. (Frontiers in Genetics, 2025)
IntroductionThe use of next-generation sequencing technologies (NGS) to study parasite populations and their response and evolution to interventions is important to support malaria control and elimination efforts. While whole-genome sequencing (WGS) is optimal in terms of assessing the entire genome, it is costly for numerous samples. Targeted approaches selectively enriching for the sequence of interest are more affordable and have higher throughput but sometimes lack adequate information content for key analyses.MethodsWe have developed a highly multiplexed molecular inversion probe (MIP) panel (IBC2FULL) targeting 4,264 single-nucleotide polymorphisms (SNPs) with ≥5% minor allele frequency (MAF) in Sub-Saharan African regions from publicly available Plasmodium falciparum WGS (n = 3,693). We optimized the panel alone and in combination with antimalarial drug resistance MIPs in laboratory P. falciparum strains at different parasitemias and validated it by sequencing field isolates from the Democratic Republic of Congo, Ethiopia, Ghana, Mali, Rwanda, Tanzania, and Uganda and evaluating the population structure, identity-by-descent (IBD), signals of selection, and complexity of infection (COI).ResultsThe new panel IBC2FULL consisted of 2,128 MIPs (containing 4,264 common SNPs) spaced by 5.1–18.4 kb across the entire genome. While these microhaplotypes were developed based on variations from Sub-Saharan African WGS data, 59.3% (2,529) of SNPs were also common in Southeast Asia. The MIPs were balanced to produce more a uniform and higher depth of coverage at low parasitemia (100 parasites/μL) along with MIPs targeting antimalarial drug resistance genes. Comparing targeted regions extracted from public WGS, we observed that IBC2FULL provided a higher resolution of the local population structure in Sub-Saharan Africa than current PCR-based targeted sequencing panels. For sequencing field samples (n = 140), IBC2FULL approximated WGS measures of relatedness, population structure, and COI. Interestingly, genome-wide analysis of extended haplotype homozygosity detected the same major peaks of selection as WGS. We also chose a subset of 305 high-performing MIPs to create a core panel (IBC2CORE) that produced high-quality data for basic population genomic analysis and accurate estimation of COI.DiscussionIBC2FULL and IBC2CORE panels have been designed to provide an improved platform for malaria genomic epidemiology and biology that can approximate WGS for many applications and is deployable for malaria molecular surveillance in resource-limited settings.